Development of selective ssDNA micro-probe for PD1 detection as a novel strategy for cancer imaging - Stanisław Malicki; Anna Czarna; Edyta Żyła; Barbara Pucelik; Wojciech Gałan; Barbara Chruścicka; Marta Kamińska; Alicja Sochaj-Gregorczyk; Katarzyna Magiera-Mularz; Jun Wang; Marek Winiarski; Małgorzata Benedyk-Machaczka; et al. (Scientific Reports)
Abstract Programmed death receptor 1, PD1, modulates the function of immune cells by providing inhibitory signals and constitutes the marker of immune exhaustion. Monitoring the level of PD1 promises a useful diagnostic approach in autoimmune diseases and cancer. Here we describe the development of an ssDNA aptamer-based molecular probe capable of specific recognition of human PD1 receptor. The aptamer was selected using SELEX, its sequence was further optimized, and the affinity and specificity were determined in biochemical assays. The aptamer was converted into a fluorescent probe and its potential in molecular imaging was demonstrated in a culture of human cells overexpressing PD1 and murine pancreatic organoids / immune cells mixed co-culture model. We conclude that the provided aptamers are suitable probes for imaging of PD1 expressing immune cells even in complex cellular models and may find future utility as diagnostic tools.